Characterization of Arbuscular Mycorrhizal Fungi associated with the green onion crop (Allium fistulosum L.) in Antioquia, Colombia - Wilches Ortiz, Wilmar (2025)
Onion crop (Allium fistulosum L.) has found an important niche in Colombian agriculture, with few studies of mycorrhizal symbiosis in productive zones. The objective of this study was to identify Arbuscular Mycorrhizal Fungi (AMF) and their relationship with agroecological zones in the onion production system. In the department of Antioquia, 23 rhizosphere soil samples were collected in lots with established onion crops for the determination of AMF, and GIS layers of the agroecological zones were applied to superimpose them. A total of 34 AMF morphospecies represented in the families Glomeraceae, Claroideoglomeraceae, Acaulosporaceae, Gigasporaceae, Ambisporaceae and Paraglomeraceae were found. The highest AMF importance value was presented by Glomus trufemii, followed by Glomus tenerum, Claroideoglomus etunicatum, Glomus microcarpum and Glomus warcupii. High affinity of the AMF Glomus sp., G. warcupii, G. halonatum, G. badium, G. ambisporum, G. macrocarpum, G. glomerulatum, Gigaspora sp., Acaulospora spp., Rhizoglomus sp. and Rhizoglomus manihotis with agricultural soils of high suitability classification for onion crops. It should be noted that the highest proportion of AMF morphospecies was associated with very low fertility soils with a greater representation of landscapes such as high plateaus, hills and hills, terraces and fan terraces. In conclusion, the importance of AMF diversity and their interaction in the green onion crop, as well as in the agroecological environment, especially in nutrient-deficient soils and erosion-prone landscapes, is highlighted.